SIMULATION MODELING OF ADJUSTABLE RAILWAY CROSSINGS - Дубровская, Татьяна; Кравченя, Ирина (SWorldJournal, 2021)
A simulation model of the movement of vehicles through adjustable railway crossings on Saltanovka – Zhlobin section in GPSS World simulation system is proposed. The developed simulation model makes it possible to determine the characteristics of crossings